Predictors of relapse following infliximab de‐escalation in patients with inflammatory bowel disease: the value of a strategy based on therapeutic drug monitoring. Issue 2 (27th December 2018) - Lucidarme, Camille; Petitcollin, Antoine; Brochard, Charlène; Siproudhis, Laurent; Dewitte, Marie; Landemaine, Amandine; Bellissant, Eric; Bouguen, Guillaume
Summary: Background: There are limited data concerning infliximab drug monitoring during de‐escalation of the treatment of inflammatory bowel disease (IBD). Aim: To define the rate and the predictors of relapse following infliximab de‐escalation in IBD patients in remission. Methods: All IBD patients at a single referral centre in clinical and biological remission and in whom the dose of infliximab had been de‐escalated were included. Patients in remission with a high trough level of infliximab (>7 mg/L) were considered to be trough level‐based de‐escalation patients. The data were retrieved from a prospective IBD database. Actuarial analysis was performed for statistical purposes. Results: A total of 146 de‐escalations were performed in 96 patients (Crohn's disease/ulcerative colitis: 68%/32%); 54 (37%) were based on clinical remission only, and 92 (63%) were based on clinical remission associated with a trough level above 7 mg/L. The cumulative probabilities of relapse following infliximab de‐escalation were 16% and 47% at 1 and 2 years, respectively. Ulcerative colitis was associated with an increased risk of relapse (HR = 3.2, P = 0.005). Conversely, combination therapy at infliximab initiation (HR = 0.39, P = 0.0110) and trough level‐based de‐escalation were associated with decreased risk of relapse (HR = 0.45, P = 0.024). Trough levels before and after de‐escalation were well correlated; a decrease by half was observed following a 2‐week interval increase or a half‐dose decrease. Conclusion: The use of trough levels to assess the feasibility of dose de‐escalation seems to be a prerequisite for decreasing the risk of relapse. Abstract : LINKED CONTENT This article is linked to Gibson and Ward and Bouguen and Siproudhis papers. To view these articles visit https://doi.org/10.1111/apt.15081 and https://doi.org/10.1111/apt.15151 .